If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5m+6=18+2m=
We move all terms to the left:
5m+6-(18+2m)=0
We add all the numbers together, and all the variables
5m-(2m+18)+6=0
We get rid of parentheses
5m-2m-18+6=0
We add all the numbers together, and all the variables
3m-12=0
We move all terms containing m to the left, all other terms to the right
3m=12
m=12/3
m=4
| 2x+(x-60)=3810 | | x-126.45=34.55 | | 5=a(81) | | 10(d-3)=37 | | 6x-3+7=6x-34-8x | | 7(y-2)=5(y-3) | | 8x-24=3x+71 | | 5(c+2)=40 | | 8x-24=3x71 | | 4b-9=4 | | 3x-3+7=4x+26-3x | | 12x+10=6x-8 | | 5=a(7+2)^2+0 | | 6t−5=2t+96t−5=2t+9 | | 5=a(9)^2 | | 405=x|-17 | | 46-26=2x | | 5(y-6)=7y+3 | | 5(y+2)=6y+1 | | 6-4x=7x-9x+10. | | (3x+16)=(8x-1) | | 12+b=8 | | x+85=x+20 | | 6(y+3)=4y+1 | | 1-x=56,7 | | 5(y+1)=4y+7 | | 4(y-7)=3y-5 | | -5(y+4)=5(y+10) | | 3n=-6+20 | | 21/r=7/6 | | 2.4+3s=-0.6, | | 2b=200 |